Primary Gastrointestinal Tract Cancers in Nigeria, Epidemiological and Histopathological Study - Uchendu, Obiora Jude; Akpo, Emmanuel Esaba (Asian Pacific Journal of Cancer Care, 2021)
Background: Cancer is a low priority health concern in Nigeria. Epidemiological and histopathological profile of primary gastrointestinal tract cancer (PGITC) is poorly characterized in this region. Aims: This paper addresses the trend, age, gender, and histological profile of PGITC in Delta State, Nigeria. Materials and Method: The study is a 75-month (2014-2020) descriptive, retrospective analysis of gastrointestinal (esophagus, stomach, intestinal and anal) cancers in Delta State University Teaching Hospital, Nigeria. Duplicate copies of histopathology reports of PGITC were examined for age, sex, site and histological diagnosis, and the results analyzed using Excel spreadsheet version 2016. Results: PGITC accounts for 15.6% of all cancers. Equal gender distribution was observed. The age range and mean age of affected patients were 23-90 years and 53.4 ±14.16 years respectively. The yearly trend undulated with two peaks in 2015 and 2019. The 3rd, 4th, 5th, 6th, 7th, 8th, 9th and 10th decades accounted for 5 (4.6%), 13 (12.0%), 21 (19.4%), 32 (29.6%), 24 (22.2%), 9 (8.3%), 3 (2.8%) and 1 (0.9%) of cases respectively. Esophageal, stomach, small intestinal, colorectal and anal cancers accounted for 6 (5.6%), 13 (12.0%), 5 (4.6%), 82 (75.9%), and 2 (1.9%) of the cases. Most colorectal and stomach cancers were adenocarcinomas. Squamous cell cancers are the most common esophageal and anal cancers while sarcomas were mostly from the small intestine. Conclusion: PGITC are relatively common in this study and mostly carcinoma with mean age and peak in the 6th decade. Colorectal cancers are distinctly the most common. There is a need for routine imaging screening to prevent gastrointestinal cancer in this region.